Zebrafish oxytocin neurons drive nocifensive behavior via brainstem premotor targets - Wee, Caroline L.; Nikitchenko, Maxim; Wang, Wei-Chun; Luks-Morgan, Sasha J.; Song, Erin; Gagnon, James A.; Randlett, Owen; Bianco, Isaac H.; Lacoste, Alix M. B.; Glushenkova, Elena; Barrios, Joshua P.; Schier, Alexander F.; et al. (Nature neuroscience, 2019)
Animals have evolved specialized neural circuits to defend themselves from pain- and injury-causing stimuli. Using a combination of optical, behavioral and genetic approaches in the larval zebrafish, we describe a novel role for hypothalamic oxytocin (OXT) neurons in the processing of noxious stimuli. In vivo imaging revealed that a large and distributed fraction of zebrafish OXT neurons respond strongly to noxious inputs, including the activation of damage-sensing TRPA1 receptors. OXT population activity reflects the sensorimotor transformation of the noxious stimulus, with some neurons encoding sensory information and others correlating more strongly with large-angle swims. Notably, OXT neuron activation is sufficient to generate this defensive behavior via the recruitment of brainstem premotor targets, whereas ablation of OXT neurons or loss of the peptide attenuates behavioral responses to TRPA1 activation. These data highlight a crucial role for OXT neurons in the generation of appropriate defensive responses to noxious input. Detecting and responding to noxious stimuli is essential for survival. Wee et al. show that noxious stimuli elicit intense and widespread activity in zebrafish oxytocin neurons, which promote defensive behavior by activating hindbrain premotor neurons.